2004
DOI: 10.1007/s00383-004-1315-3
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of parafollicular thyroid C-cells in experimental esophageal atresia: further evidence of a neural crest pathogenic pathway

Abstract: Adriamycin-induced experimental esophageal atresia (EA) is often associated with malformations of neural crest (NC) origin, such as abnormal pharyngeal pouch derivatives like the thymus and the parathyroids. The aim of the present study was to examine whether NC-derived thyroid C-cells were abnormal in a rat model. Pregnant rats received intraperitoneally either 2 mg/kg Adriamycin (EA) or vehicle (controls) on days 8 and 9 of gestation. Fetuses were recovered on day 21, and blocks including the trachea and thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…No correlation was seen between intracellular Tn-C expression with any of the investigated clinicopathologic parameters and stromal Tn-C expression. Due to the expression of tenascin in neural crest cells, the expression in C cells may be an incidental phenomenon due to its neurocrest origin [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…No correlation was seen between intracellular Tn-C expression with any of the investigated clinicopathologic parameters and stromal Tn-C expression. Due to the expression of tenascin in neural crest cells, the expression in C cells may be an incidental phenomenon due to its neurocrest origin [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…The scarcity of thyroid CC in infants with CDH represents the fi rst evidence of yet another neural crest signaling anomaly in CDH patients, mediated very likely by similar dysfunctions in embryogenic control. It should be pointed out that CC scarcity has been found in other human conditions where NC signaling was defi cient such as DiGeorge syndrome or conotruncal cardiac defects [10,11] , and also in a rat model of esophageal atresia where elements of NC control dysfunction are present as well [33] .…”
Section: Discussion ▼mentioning
confidence: 99%
“…In the experimental setting, it has been shown that rats exposed in utero to adriamycin have EA-TEF and very high proportions of absence, hypoplasia or ectopy of the thymus, and parathyroids [81]. We recently investigated the C-cells of the thyroid in this rat model and found that they were drastically reduced in animals with EA-TEF [82]. We do not know whether this happens in patients with EA-TEF, but there is some evidence pointing in that direction: the autopsies of 11 cases of Di George syndrome from our own institution (several of which had EA-TEF) showed decreased number of C-cells in their thyroids [83], and similar findings were reported for patients with conotruncal heart malformations that are frequently associated to EA-TEF [84].…”
Section: Esophageal Atresia-tracheoesophageal Fistulamentioning
confidence: 96%